Quantitative Imaging of D-2-Hydroxyglutarate in Selected Histological Tissue Areas by a Novel Bioluminescence Technique - Voelxen, Nadine F.; Walenta, Stefan; Proescholdt, Martin; Dettmer, Katja; Pusch, Stefan; Mueller-Klieser, Wolfgang (Frontiers in Oncology, 2016)
Abstract Patients with malignant gliomas have a poor prognosis with average survival of less than one year. Whereas in other tumor entities the characteristics of tumor metabolism are successfully used for therapeutic approaches, such developments are very rare in brain tumors, notably in gliomas. One metabolic feature characteristic of gliomas, in particular diffuse astrocytomas and oligodendroglial tumors, is the variable content of D-2-hydroxyglutarate (D2HG), a metabolite, which was discovered first in this tumor entity. D2HG is generated in large amounts due to various “gain-of–function” mutations in the isocitrate dehydrogenases IDH-1 and IDH-2. Meanwhile, D2HG has been detected in several other tumor entities including intrahepatic bile-duct cancer, chondrosarcoma, acute myeloid leukemia, and angioimmunoblastic T-cell lymphoma. D2HG is barely detectable in healthy tissue (< 0.1 mM), but its concentration increases up to 35 mM in malignant tumor tissues. Consequently, the “oncometabolite” D2HG has gained increasing interest in the field of tumor metabolism. To facilitate its quantitative measurement without loss of spatial resolution at a microscopical level, we have developed a novel bioluminescence assay for determining D2HG in sections of snap-frozen tissue. The assay was verified independently by photometric tests and liquid chromatography / mass spectrometry (LC/MS). The novel technique allows the microscopically resolved determination of D2HG in a concentration range of 0 – 10 µmol/g tissue (wet weight). In combination with the already established bioluminescence imaging techniques for ATP, glucose, pyruvate, and lactate, the novel D2HG assay enables a comparative characterization of the metabolic profile of individual tumors in a further dimension.